Disentangling Fabiana imbricata (Solanaceae) regeneration: the importance of disturbance and rainfall - Ghermandi, Luciana (2013)
In Mediterranean ecosystems, fire influences plant population dynamics and changes plant communitystructure by affecting germination and establishment of seeder shrubs. Fabiana imbricata is a long-lived seeder shrub with a broad distribution in South America. In Northwestern Patagonia grasslands there are many records of F. imbricata recruitment after fires.We hypothesized that recruitment is promoted by: 1)soil erosion that exposes deeply buried seeds; 2) direct fire effects such as heat that could break seed dormancy; 3) indirect fire effects (i.e. increase of light availability and elimination of allelopathic substances)and 4) water availability in spring. In field conditions, we tested the effects of shading and soildisturbance on F. imbricata recruitment and seed availability and distribution in the soil profile. Under controlled conditions, we investigated the influence of leaf leachate, light, heat and water on seed germination and seedling emergence. Seed germination was inhibited by leachate, and seedling emergence was inhibited by seed heated to 80 C and 120 for 5 min. F. imbricata seedlings only emerged in germination treatments that simulated wet and very wet spring conditions. Fire and postfire wind that favor seed exposure, combined with high precipitation early in the growing season, would be necessary for successful shrub recruitment. When F. imbricata shrubland colonizes the grassland, it strongly modifies local vegetation structure, reduces species richness and increases fuel loads. F. imbricata is a key species in the ecosystem specially related to fire regime. Information on the postfire regeneration of this species would provide valuable knowledge of the changes in biomass accumulation in a fire-prone Mediterranean ecosystem.